Decoding the immune microenvironment in osteosarcoma: new insights into checkpoints, vaccines, and CAR-T cells - Wang, Haitian; Zhu, Tongtong; Yang, Kunpeng; Xu, Chenkai; Zhang, Zhaoyi; Liu, Guangyao; Ren, Hongge (Frontiers in Oncology, 2025)
Osteosarcoma (OS), the most prevalent primary malignant bone tumor, disproportionately affects adolescents and is marked by rapid progression and a high rate of pulmonary metastasis. Despite advances in multimodal treatment, outcomes remain dismal for metastatic or relapsed disease, largely due to chemoresistance, immune evasion, and the heterogeneous tumor microenvironment (TME). Increasing evidence underscores the immunoregulatory complexity of osteosarcoma, characterized by immunosuppressive myeloid-derived populations, dysfunctional lymphocyte infiltration, and exosome-mediated immune escape. While immune checkpoint inhibitors have revolutionized treatment in several malignancies, their impact in osteosarcoma remains modest, highlighting the need for combinatorial strategies. Emerging approaches such as adoptive T cell therapies, tumor vaccines, and CAR-T cell interventions are being explored to overcome the “cold” immune milieu. Furthermore, single-cell transcriptomics has shed light on cellular interactions within the osteosarcoma TME, offering insights into resistance mechanisms and potential biomarkers. This review provides a comprehensive overview of the immunological landscape of osteosarcoma and highlights current and emerging immunotherapeutic strategies aimed at improving clinical outcomes in this challenging malignancy.